4-Methylguaiacol alleviated alcoholic liver injury by increasing antioxidant capacity and enhancing autophagy through the Nrf2-Keap1 pathway. (February 2023) - Li, Anjun; Chen, Shanbin; Yang, Zhen; Luan, Chunguang; Lu, Wei; Hao, Feike; Tang, Youhong; Han, Xinlin; Wang, Deliang
Abstract: It is now well established that alcoholic liver disease is associated with oxidative stress and inflammatory reactions. 4-Methylguaiacol (4 MG) is a phenolic lignin model compound found in many foods. In this study, the effect of 4 MG on antioxidant capacity was evaluated and the molecular mechanisms of autophagy and the Keap1-Nrf2 signaling pathway were explored in vitro and in vivo . The in vitro results showed that 4 MG possessed strong free radical scavenging capabilities in LO2 cells treated with 2, 2′-azobis-2-methyl-propanimidamide (AAPH) by dramatically repressing the expression of malondialdehyde and upregulating superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px). Under both starvation and full nutrition conditions, pretreatment of LO2 cells with 4 MG remarkably increased the level of autophagy by promoting the expression of microtubule-associated protein 1 light chain 3-II (LC3-II) and decreasing the level of sequestosome-1 (p62) protein. Additionally, when exposed to AAPH, 4 MG further promoted the expression of LC3 at the mRNA level, while IL-1β, IL-6, NF-κB, and TNF-α were inhibited. This result was confirmed by a fluorescence confocal experiment. The in vivo results further revealed that the administration of 4 MG significantly attenuated serum liver enzyme and lipid levels in alcoholic liver injury mouse model. Meanwhile, the levels of serum high-density lipoprotein-cholesterol and hepatic SOD, CAT, and GSH-Px were upregulated. Autophagy was promoted after the administration of 4 MG compared with the enhanced autophagy group (Torin1 group). Furthermore, the entry of Nrf2 protein into the nucleus was accompanied by a reduction of Keap1 and the increased expression of the downstream heme oxygenase 1 (HO-1). These results revealed that 4 MG partially improved the antioxidant capacity through the Keap1-Nrf2 pathway in the liver. Thus, 4 MG is a natural product with potentially liver-protective effects.